Westonci.ca offers quick and accurate answers to your questions. Join our community and get the insights you need today. Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
The Laplace transform of the given function is [tex]f(s)=\frac{1-e^{-5s}(1-5s) }{s^{2} }[/tex]
Given,
[tex]f(t)=\left \{ {{t, 0\leq t < 5} \atop {0,t\geq 5}} \right.[/tex]
Write the function in unit step function.
[tex]f(t)=t(u_{0}(t)-u_{5} (t))[/tex]
= [tex]t(1-u_{5}(t))[/tex] ∵[tex]u_{0} (t)=1[/tex]
= [tex]t-tu_{5} (t)[/tex]
[tex]f(t)=t-tu_{5} (t)[/tex]
In order to make it easier to take the Laplace transform of the function, we can follow the steps:
[tex]f(t)=t-tu_{5} (t)[/tex]
= [tex]t-(t-5+5)u_{5} (t)[/tex]
= [tex]t-(t-5)u_{5} (t)+5u_{5} (t)[/tex]
[tex]f(t)=t-(t-5)u_{5} (t)+5u_{5} (t)[/tex]
We need to find the Laplace transform of f(t).
Apply Laplace transform on both sides,
£[tex][f(t)=[/tex]£[tex](t)-[/tex]£[tex](t-5)u_{5} (t))+5[/tex]£[tex](u_{5} (t))[/tex]
= [tex]\frac{1}{s^{2} } -e^{-s}[/tex]£[tex](t)+5(\frac{e^{-5s} }{s} )[/tex]
= [tex]\frac{1}{s^{2} } -e^{-5s} (\frac{1}{s^{2} } )+\frac{5se^{-5s} }{s^{2} }[/tex]
= [tex]\frac{1-e^{-5s}+5se^{-5s} }{s^{2} }[/tex]
= [tex]\frac{1-e^{-5s}(1-5s) }{s^{2} }[/tex]
[tex]f(s) =\frac{1-e^{-5s}(1-5s) }{s^{2} }[/tex]
Learn more about Laplace transform here: https://brainly.com/question/17190535
#SPJ4
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.